English-Indonesian Subtitling Strategies of Lara Jean’s Utterances in “To All the Boys: Always and Forever” Movie on Netflix - Tiffani Rizki Putri Baihaqi; Agus Subiyanto (Universitas Dian Nuswantoro, 2021)
Abstract. Streaming platforms, such as Netflix, gained their popularity significantly during the pandemic prominently since people avoid watching films in theatres. Thus, the study of translation, specifically subtitling, is necessary since there will be more films with different languages to be produced and streamed by people from different countries. This research aims to study and interpret the subtitling strategies used on Netflix, specifically in “To All the Boys: Always and Forever” movie. Employing a qualitative library research method and document analysis for the data collecting technique, this research unveils the subtitling strategies as well as the subtitle quality of Lara Jean’s utterances in “To All the Boys: Always and Forever” film on Netflix. The data source is chosen since the film is considered popular as it is the adaptation of the best-selling novel “Always and Forever, Lara Jean.” From the 428 utterances, it is discovered that there are seven strategies applied; respectively paraphrase, transfer, condensation, deletion, expansion, imitation, and transcription. Meanwhile, three strategies that are not found are decimation, dislocation, and resignation. Paraphrase is the most frequently applied strategy since many utterances require localization and alteration to become clearer for the Indonesian audience. On the other hand, decimation, dislocation, and resignation are not used respectively due to the rate of the film, translatable utterances, and soundtracks that are not translated.Keywords: film; netflix; subtitling strategies; subtitling quality; translationAbstrak. Layanan streaming, seperti Netflix, meraih popularitas secara signifikan selama pandemi karena masyarakat menghindari menonton film langsung di bioskop. Oleh karena itu, penelitian mengenai terjemahan, khususnya subtitling, diperlukan karena film dalam bahasa asing akan semakin banyak diproduksi dan ditonton oleh orang-orang dari berbagai negara. Penelitian ini bertujuan untuk mengkaji dan memaknai strategi subtitling yang digunakan oleh Netflix, khususnya pada film “To All the Boys: Always and Forever.” Penelitian ini menggunakan metode deskriptif kualitatif dan mengungkap strategi serta kualitas subtitling dari ucapan Lara Jean dalam trilogi “To All the Boys: Always and Forever” di Netflix. Sumber data tersebut dipilih karena film yang dianggap populer ini merupakan adaptasi dari novel “Always and Forever, Lara Jean.” Dari 428 ujaran, terdapat tujuh strategi yang diterapkan, yaitu parafrase, transfer, pemampatan, penghapusan, penambahan, imitasi, dan transkripsi. Sedangkan tiga strategi yang tidak diterapkan yaitu desimasi, dislokasi, dan angkat tangan. Parafrase merupakan strategi yang paling banyak ditemukan karena terdapat banyak ujaran yang disesuaikan dengan konteks lokal dan diubah agar menjadi lebih jelas bagi penonton Indonesia. Sementara itu, desimasi, dislokasi, dan angkat tangan tidak digunakan karena kategori film, ujaran yang dapat diterjemahkan, dan lagu yang tidak diterjemahkan.Kata kunci: film; kualitas subtitling; netflix; strategi subtitling; terjemahan